1997
DOI: 10.1038/hdy.1997.104
|View full text |Cite
|
Sign up to set email alerts
|

Inheritance and linkage of isozymes in Yponomeuta padellus (Lepidoptera, Yponomeutidae)

Abstract: Inheritance and genetic linkage of 29 allozyme loci were studied by single-pair crosses of Yponomeuta padellus (Lepidoptera, Yponomeutidae). All loci segregated as Mendelian genes with codominant alleles except for a null allele at the hbdh locus. The three loci est-2, 6pgdh, and fudh were sex-linked and occurred in that order along the Z chromosome. Autosomal linkage analysis was facilitated by the lack of crossing-over in females characteristic of Lepidoptera, because linkage in female-informative crosses is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Because discerning the sex of the sampled individual would make these data more meaningful in the context of dosage compensation, we assayed SNPs in the data, assuming that only a male would show heterozygosity on the Z. This is a reasonable assumption given that there is ample allozyme evidence for diploid, heterozygous expression of Z-linked loci in male Lepidoptera ( Mallet et al 1993 ; Raijmann et al 1997 ); there is also little evidence for any Z-W homology in Bombyx so it is unlikely that apparent Z-linked heterozygosity could arise from pseudoautosomal regions such as occurs between X and Y chromosomes in humans ( Fujii and Shimada 2007 ). We identified 182 heterozygous Z-linked SNPs, a count which falls squarely in the range detected among autosomes using the same criteria (132–569 SNPs per chromosome).…”
Section: Resultsmentioning
confidence: 99%
“…Because discerning the sex of the sampled individual would make these data more meaningful in the context of dosage compensation, we assayed SNPs in the data, assuming that only a male would show heterozygosity on the Z. This is a reasonable assumption given that there is ample allozyme evidence for diploid, heterozygous expression of Z-linked loci in male Lepidoptera ( Mallet et al 1993 ; Raijmann et al 1997 ); there is also little evidence for any Z-W homology in Bombyx so it is unlikely that apparent Z-linked heterozygosity could arise from pseudoautosomal regions such as occurs between X and Y chromosomes in humans ( Fujii and Shimada 2007 ). We identified 182 heterozygous Z-linked SNPs, a count which falls squarely in the range detected among autosomes using the same criteria (132–569 SNPs per chromosome).…”
Section: Resultsmentioning
confidence: 99%
“…The accumulation of gene complexes on the Z chromosome could facilitate host shifts, because in the heterogametic sex co-adaption of multiple host use, loci would not be disrupted by recombination (Hagen & Scriber, 1995). However, it is unclear why this phenomenon should be especially pronounced in Lepidoptera (Pashley-Prowell, 1998), since in this insect order female autosomes do not undergo recombination either (Traut & Marec, 1996;Raijmann et al, 1997), and linkage groups will therefore be favoured equally on autosomes and sex chromosomes. Charlesworth et al (1987) showed that the rate of evolution of favourable autosomal mutations exceeds that of X-linked loci if they are semi-dominant or dominant, especially if selection acts on the heterogametic sex.…”
Section: Inheritance Of Adult Host Acceptancementioning
confidence: 99%
“…There is tentative evidence that lepidopteran Z chromosomes do diverge faster than the autosomes, as many species-diagnostic traits are Z linked, including 24% of differentiated allozyme loci across 11 species comparisons (Sperling 1994;Prowell 1998). However, in Lepidoptera, which generally have chromosome numbers around 30, between 10% and 25% of all polymorphic allozyme loci are Z linked (Mallet et al 1993;Raijmann et al 1997;D. Heckel, pers.…”
Section: Lepidoptera and Alternative Causes Of Haldane's Rulementioning
confidence: 99%